Factors Influencing Uptake of Post-Partum Family Planning Among Mothers 0- 6 Weeks Postpartum at Kiryandongo Hospital. A Cross-Sectional Study. - Akello, Florence; Okorid, Felex (Student's Journal of Health Research Africa, 2023)
Background: Postpartum period is a critical time to address the unmet family planning needs and reduce the risk of too-soon pregnancies, maternal and child morbidity, and mortality. The study was conducted to determine the factors influencing the uptake of postpartum family planning among postpartum mothers 0 to 6 weeks postpartum Method: The study was a cross-sectional study that employed quantitative methods for data collection. 56 postpartum mothers present at the study area at the time of data collection were counseled and interviewed using a semi-structured questionnaire. Result: There is a significant association between age and uptake of PPFP where mothers at a younger age are more likely to use PPFP within 6 weeks after delivery [x2(1) =6.222a; p<0.045], between religion and uptake of PPFP [x2(1) =6.257a; p<0.044]. Also, a significant association between attitude and uptake of PPFP where mothers who perceived PPFP to be both very good and good are more likely to use PPFP [x2(1) =7.840a; p<0.020]. In the same way, challenges such as inadequate counseling, long waiting time, inadequate staffing, and uncooperative health workers may affect the use of PPFP within 6 weeks after delivery [x2(1) =10.114a; p<0.039]. Conclusion: Commonly identified socio-demographic factors including age groups, religion, and attitude were significantly associated with the utilization of PPFP within 0-6 weeks. These socio-demographic factors are made worst by some health facility factors such as inadequate counseling of mothers, uncooperative health workers, and often few skilled service providers leading to over waiting by the clients. Recommendation: Strengthening the health facility’s ability to adequately disseminate accurate information to mothers and the community at large concerning IPPFP. Healthcare providers should build the capacity of community health workers to promote effective community awareness about PPFP and its advantages to families and society at large.
Factors Influencing Uptake of Post-Partum Family Planning Among Mothers 0- 6 Weeks Postpartum at Kiryandongo Hospital. A Cross-Sectional Study
Keywords: Postpartum family planning; Postpartum period (06 weeks); Family planning